PENGARUH PERCERAIAN PADA ANAK USIA DINI - Srinahyanti Srinahyanti (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACT Divorce is the legal dissolution of a marriage relationship by a court and almost half of divorce happen in the first 10 years of marriage, it mean that children from divorced families are still at an early age. This means that daily interaction and communication between children with one of the parents will be reduced that can decreasing the attachment of the child to the parent and child trust affect against theirself. In addition, the child will be exposed to the fickle conditions, psychic tendencies negative emotions and aggressive behavior will appear on children as a victims of divorce. Keywords: Parental Divorce, Early Childhood